Outcomes in Patients with a Calipered Kinematically Aligned TKA That Already Had a Contralateral Mechanically Aligned TKA - Shelton, Trevor J.; Gill, Manpreet; Athwal, Gurbir; Howell, Stephen M.; Hull, Maury L. (The Journal of Knee Surgery, 2019)
Prior studies suggest kinematically aligned (KA) total knee arthroplasty (TKA) provides some clinical benefits. There are no reports of self-reported outcome measures in patients treated with a calipered KA TKA that already had a contralateral mechanically aligned (MA) TKA. We performed a retrospective study and asked the following questions: (1) Were you satisfied with your MA TKA when you were treated with the KA TKA? (2) What are the Forgotten Joint Scores (FJS) and Oxford Knee Scores (OKS) in each of your knees? (3) Do you favor one knee? and (4) Did one knee recover faster? From January 2013 to January 2017, 2,378 consecutive primary TKAs were performed of which all were treated with calipered KA that uses serial verification checks incorporating measurements of bone resections and positions to restore the prearthritic or native joint lines accurately. A records review identified patients with a prior primary MA TKA in the contralateral limb. Excluded were those with a history of fracture, osteotomy, infection, or revision knee surgery in either limb. In September 2018, 78 patients (57 females) with a mean age of 73 years (range, 50–91 years) completed a follow-up evaluation consisting of the FJS and OKS questionnaires and three anchor questions. A total of 83% of patients were satisfied with the MA TKA and 92% were satisfied with the KA TKA. The KA TKA had a 15 point higher median FJS and a comparable OKS to that of the MA TKA. Also, 56% of patients favored the KA TKA, and 8% favored the MA TKA. Seventy four percent of patients favored the recovery of the KA TKA, and 6% favored the recovery of the MA TKA. Accordingly, a patient considering a contralateral KA TKA can expect that more often than not the KA TKA will have a higher FJS, a similar OKS, be their favorite knee, and recover faster. Present study is therapeutic and reflects level IV evidence.
Keywords: knee arthroplasty; kinematic alignment; Oxford knee score